Nutrient cycle in an integrated recirculating aquaculture system - Le Van, Khoi (Curtin University, 2012)
Intensive marine aquaculture may cause negative impacts on the aquatic environment by causing water pollution, algae bloom and reduction in biodiversity of the surrounding aquatic environment. The nutrient-rich effluents from aquaculture activities contain nitrogen and phosphate which serve as a nutrient source for bivalve, algae and invertebrates. Seaweed and mussels have been integrated with marine species in culture systems to remove the waste from aquaculture farms. The research has explored the nutrient uptake capacities of green seaweed (Ulva lactuca) and blue mussel (Mytilus edulis) integrated with western king prawn (Penaeus latisulcatus) in the integrated closed recirculating aquaculture systems (IRAS) and has evaluated the nutrient retention of seaweed and animals in the system.One experimental unit of an IRAS consisted of three tanks: a mussel tank, a prawn tank and a waste-collection tank. The mussel tank and the prawn tank were set on the top and lower tiers of a metal frame; the waste-collection tank was on the floor. Water was pumped from the waste-collection tank to the reservoir tank by a submersible pump, circulated to the prawn tank and then returned to the waste collection tank through gravity.A series of experiments were conducted under laboratory conditions to investigate the water quality; survival, growth of western king prawn and nutrient budget in the IRAS. The research results proved that the recirculating culture system could maintain acceptable water quality for western king prawn at stocking densities till 16 prawn m-2 and at feeding rate of 3.0% of wet weight biomass. Increasing the stocking densities results in decreasing the water quality in the culture media, the growth and survival of western king prawn reared in the recirculating aquaculture system. In contrast, increasing feeding rate did not improved growth and survival rate of western king prawn but feed utilization efficiency decreased significantly with increasing the feeding rates. Total phosphorus (TP) and orthophosphate (PO43-) concentrations increased linearly with increasing the feeding rates of western king prawn. High percentage of nutrient inputs accumulated into tank bottom at higher stocking densities whereas over 50% of nutrient inputs were in discharged water at harvest in lower stocking densities.Inclusion green seaweed into western king prawn culture system improved the water quality in the IRAS. Concentrations of total ammonia nitrogen (TAN), nitrate (NO3-) and PO43- in the integrated culture system were lower than those in the monoculture system. Green seaweed effectively removed 24.02-99.05% TAN and 13.80-96.40% PO43- in the culture media. Feed utilization efficiency in integrated culture was significantly enhanced by 24.90 % nitrogen (N) and 19.41% phosphorus (P). Nutrient budget revealed that western king prawn and green seaweed retained 28.00-31.90% and 6.53-29.71% N of total nitrogen (TN) inputs at harvest, respectively while P retention was 13.46-14.63% and 1.62-13.50% of TP inputs, respectively. The rest of total nutrient input was in discharged water and tank sediments.Integrated culture of blue mussel and western king prawn could improve the water quality in the IRAS though effectively removing of the total bacteria (TB), total suspended solids (TSS) and total nitrogen (TN) in the cultured media. However, concentrations of NO2-, NO3- and PO43- were increased due to the mussel excretion. Growth and survival of western king prawn were not affected by adding blue mussels into western king prawn culture in IRAS at stocking rate of 250 mussel m-2 and 16.07 prawn m-2. When stocking rates exceed density of 312.5 mussel m-2 and =21.36 prawn m-2, growth and survival of both western king prawn and blue mussel in the IRAS were declined significantly due to the low water quality and crowded effects in the culture media. Inclusion of blue mussels into western king prawn culture was enhanced the feed utilization efficiency further up to 10.63 % N and 4.89 % P and reduced the nutrient discharged through draining at harvest. N and P contents accumulated in mussel tanks increased linearly with the increasing mussel stocking densities in the IRAS. The results indicate that the use of integrated aquaculture system is a step forward to achieve sustainability in aquaculture.